(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
The study was designed to evaluate knowledge, attitude and practice of future prescribers of four Medical Colleges of Chittagong, Bangladesh about Pharmacovigilance. The specific aim was to identify the reasons for underreporting and to determine the measure that could be adopted to increase reporting of ADRs (Adverse Drug Reactions). A crosssectional, multicenter Questionnaire survey was conducted among the final year medical students and intern doctors to assess the knowledge and attitude regarding the importance of ADRs reporting and Pharmacovigilance of Chittagong Medical College (CMC) Chattagram Maa-OShishu Hospital Medical College (CMOSHMC) Cox’s Bazar Medical College (CoxMC) Southern Medical College (SMC) during July, 2015. The questionnaires were provided to five hundred and eight participants of which two twenty four final year students and one hundred fifty six intern of four medical colleges responded completely to the survey. 65% responders were aware of the term Pharmacovigilance. Only one third of respondent correctly answer the location of international (35% intern and 25% final year) and national ADRs monitoring centre (24% intern and 35% final year). Almost all participants (100%) had no training on ADRs reporting and did not see any ADRs reporting form in their study period. Majority (96%) of the respondent felt that study related to antibiomicrobials should be thought in details to all health care students during their undergraduate training period. The major cause of under reporting in their views is insufficient knowledge about how to report (89%) and difficult to diagnosis ADRs (50%). The study revealed a deficiency of knowledge, attitude and practice about ADR reporting and Pharmacovigilance. In order to have a successful Pharmacovigilance program, future prescribers need education, training and motivation about reporting of ADRs and Pharmacovigilance with an ultimate direction towards ensuring patient safety. Best intervention will be made by training of our future prescribers during their study period. JCMCTA 2016 ; 27 (1) : 4 - 10